Tinjauan Konseling Pastoral Terhadap Dinamika Pernikahan: Perspektif Teologis dalam Membangun Hubungan Harmonis - Lily Peggy Kawatu; Eddy Simanjuntak; Herman Pakiding; Juan Carlos (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
Marriage is the union of two individuals in a sacred life together, but is often tested by various challenges. Pastoral counseling is a solution to help couples overcome problems and build a harmonious relationship. A theological perspective provides a strong spiritual and moral foundation in forming a healthy marital relationship. It views marriage as a spiritual calling, where partners are united by God to complement each other on a spiritual journey. The moral foundation of religious teachings becomes a guide in resolving conflicts and making constructive decisions. Prayer is a means of communication with God, providing guidance and strength in facing problems. Forgiveness and unconditional love are important values taught by religion, helping couples navigate conflict wisely. Pastoral counseling with a theological approach helps couples overcome marital dynamics by strengthening their relationship in accordance with the principles of religious teachings.